Enhancing Marketing Performance Through Competitive Advantage Based on Entrepreneurial Orientation and Market Orientation (A Study on the Footwear Industry in Banten Province) - Kencana, Putri Nilam; Diposumarto, Ngadino Surip; Farradia, Yuary (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze and verify the impact of entrepreneurial orientation and market orientation on competitive advantage and its subsequent effect on marketing performance in the footwear industry in Banten Province. The research design employed a causal approach. The population consisted of all entrepreneurs in the footwear industry within Banten Province, with a sample size of 140 respondents. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The research findings indicate that, in the footwear industry in Banten Province, entrepreneurial orientation has a positive and significant impact on competitive advantage, market orientation has a positive and significant impact on competitive advantage, competitive advantage has a positive and significant impact on marketing performance, entrepreneurial orientation greatly and positively influences marketing performance, market orientation does not significantly improve marketing performance, and entrepreneurial orientation greatly and positively influences marketing performance through competitive advantage.